Hydrophobic coatings from photochemically prepared hydrophilic polymethacrylates via electrospraying. Issue 8 (3rd February 2017) - Isık, Tuğba; Demir, Mustafa M.; Aydogan, Cansu; Ciftci, Mustafa; Yagci, Yusuf
ABSTRACT: Linear poly(hydroxyethyl methacrylate‐co‐methyl methacrylate) P(HEMA‐co‐MMA) and poly(dimehylaminoethyl methacrylate‐co‐methyl methacrylate) P(DMAEMA‐co‐MMA) and their corresponding hyperbranched copolymers were synthesized by conventional photoinitiated free radical polymerization and self‐condensing vinyl polymerization (SCVP) using Type I and Type II photoinitiators, respectively. Then, the polymers were processed by electrospraying in N, N ‐dimethylformamide. The surface of the resulting electrospray coatings was examined by SEM, XPS, and WCA then compared with those prepared by drop casting. Regardless of the structural nature of the polymers, electrospraying allows the preparation of rough surface that shows more hydrophobic behavior. Electrospray coatings with linear and hyperbranched copolymers exhibited WCA as ∼150° and ∼130°, respectively, indicating that branching reduces the WCA. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 1338–1344 Abstract : The water contact angle (WCA) of hydrophilic surfaces prepared from PMMA‐based linear and hyper‐branched copolymers was improved by virtue of electrospraying. This cost effective approach has no need for such chemical treatments, harsh experimental procedures, fluorine attachment, or lithographic techniques.